2012
DOI: 10.1111/j.1399-0039.2012.01930.x
|View full text |Cite
|
Sign up to set email alerts
|

The frequencies of human neutrophil alloantigens among the Japanese population

Abstract: Human neutrophil antigens (HNAs) play an important role in a variety of clinical conditions including immune‐mediated neutropenia, non‐hemolytic transfusion reactions, and transfusion‐related acute lung injury. The aim of this study was to investigate the frequency distribution of HNAs‐1 to ‐5 among the Japanese population. We analyzed samples from 570 healthy Japanese by molecular and serologic techniques to estimate the gene frequencies of HNAs‐1 to ‐5. DNA samples were obtained and typed for the HNA‐1 (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
52
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(71 citation statements)
references
References 30 publications
14
52
1
4
Order By: Relevance
“…The HNA‐3b/3b genotype frequency among the Zhuang population is 8.6%, which is similar to the frequencies reported in the Dong population of our study and also other Asian populations like Chinese Han, Japanese and Thai shown by previous publications (Changsri et al., ; Matsuhashi et al., ; Xia et al., ) but is significantly higher than that of African American Shown by Huvard et al. (), Brazilian as shown by Lopes et al.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The HNA‐3b/3b genotype frequency among the Zhuang population is 8.6%, which is similar to the frequencies reported in the Dong population of our study and also other Asian populations like Chinese Han, Japanese and Thai shown by previous publications (Changsri et al., ; Matsuhashi et al., ; Xia et al., ) but is significantly higher than that of African American Shown by Huvard et al. (), Brazilian as shown by Lopes et al.…”
Section: Discussionsupporting
confidence: 91%
“…(), the Japanese populations as reported by Matsuhashi et al. () and also the Thai population (Nathalang, Intharanut, Siriphanthong, & Leetrakool, ); However, the 457C>T substitution was found in German population as reported by Flesch et al. () and the African American blood donors as shown by Huvard et al.…”
Section: Discussionmentioning
confidence: 82%
“…In this study, we developed a new method, EGIFA, to detect anti‐HNA‐1a, ‐1b, and ‐2 antibodies simultaneously. We focused on anti‐HNA‐1a, ‐1b, and ‐2 antibodies because the majority of anti‐HNA antibodies detected in Japanese patients with immune neutropenias are anti‐HNA‐1a, ‐1b, or ‐2 based on the frequency of HNA types in Japan . To evaluate the reliability of EGIFA, we compared the results of EGIFA with the results obtained from several conventional methods.…”
Section: Discussionmentioning
confidence: 99%
“…Among Africans and Caucasians, HNA‐1b is more frequent than HNA‐1a. In contrast, in Asians and Amerindians, HNA‐1a is more frequent than HNA‐1b . HNA‐1c is most often found among Africans (20%–30%) and Caucasians (5–10%), while it is very rare in Asians (<1/500) .…”
Section: Introductionmentioning
confidence: 91%